Handbook of organopalladium chemistry for organic synthesis - Negishi, Ei-ichi 1935-2021; Meijere, A. de (Wiley-Interscience, 2002)
This handbook is organized to provide maximum utility to the bench synthetic chemist. The editor is well-known for his work in exploring, developing, and applying organopalladium chemistry and its contributors include over 24 world authorities in the field.